In situ forming microporous gelatin methacryloyl hydrogel scaffolds from thermostable microgels for tissue engineering. Issue 3 (2nd September 2020) - Zoratto, Nicole; Di Lisa, Donatella; de Rutte, Joseph; Sakib, Md Nurus; Alves e Silva, Angelo Roncalli; Tamayol, Ali; Di Carlo, Dino; Khademhosseini, Ali; Sheikhi, Amir
Abstract: Converting biopolymers to extracellular matrix (ECM)‐mimetic hydrogel‐based scaffolds has provided invaluable opportunities to design in vitro models of tissues/diseases and develop regenerative therapies for damaged tissues. Among biopolymers, gelatin and its crosslinkable derivatives, such as gelatin methacryloyl (GelMA), have gained significant importance for biomedical applications due to their ECM‐mimetic properties. Recently, we have developed the first class of in situ forming GelMA microporous hydrogels based on the chemical annealing of physically crosslinked GelMA microscale beads (microgels), which addressed several key shortcomings of bulk (nanoporous) GelMA scaffolds, including lack of interconnected micron‐sized pores to support on‐demand three‐dimensional‐cell seeding and cell–cell interactions. Here, we address one of the limitations of in situ forming microporous GelMA hydrogels, that is, the thermal instability (melting) of their physically crosslinked building blocks at physiological temperature, resulting in compromised microporosity. To overcome this challenge, we developed a two‐step fabrication strategy in which thermostable GelMA microbeads were produced via semi‐photocrosslinking, followed by photo‐annealing to form stable microporous scaffolds. We show that the semi‐photocrosslinking step (exposure time up to 90 s at an intensity of 100 mW/cm 2 and a wavelength of 365 nm) increases the thermostability of GelMA microgels while decreasing their scaffold forming (annealing) capability. Hinging on the tradeoff between microgel and scaffold stabilities, we identify the optimal crosslinking condition (exposure time 60 s) that enables the formation of stable annealed microgel scaffolds. This work is a step forward in engineering in situ forming microporous hydrogels made up from thermostable GelMA microgels for in vitro and in vivo applications at physiological temperature well above the gelatin melting point.